Doing medicine together : Germany and Russia between the wars - Solomon, Susan Gross (German and European studies., 2006)
Analyzes aspects of the German-Russian collaboration often overlooked by students of cross-national science, including the choice of 'friends' across borders, the activities of scientific entrepreneurs, the tensions between bi-lateral and international science, and the migration of scientists.